(untitled) (American Journal of Islam and Society, 2015)
In this extension of her important 2002 article in American Anthropologist, Lila Abu-Lughod examines the problematic nature of the western discourse surrounding Muslim women. In particular, she is interested in how western political programs in countries like Iraq and Afghanistan use the status of girls and women to validate their claims to occupy, colonize, or otherwise meddle in Muslim countries’ internal affairs. Abu-Lughod shows how the human rights discourse surrounding grim situations (often aggravated or caused by western interventions and other maneuverings) relies on a kind of one-downtrodden-Muslim-female-fits-all scenario. This book analyzes the “idea of the Muslim woman,” a character often in need of western liberation, and argues that the lives of Muslims are more complicated and nuanced than the popular media would have us believe. Abu-Lughod begins her Introduction by reflecting on her fieldwork as an anthropologist in Egypt, an experience that taught her a great deal about the lives of Muslim women and has influenced her view that there is a “disjuncture between my experiences and these public attitudes” (p. 4). In other words, what the West thinks about Muslim women – their hopes, dreams, aspirations, and experiences – is radically different than what Muslim women actually experience. These fantasies, much like the fantasies about Muslim men as irrational and hopelessly violent, “rationalize American and European international adventures across the Middle East and South Asia” (p. 7). Muslim women are represented as lacking agency, a result in part of the alignment of sexual freedoms with personal liberation, about which Wendy Brown has written. Abu- Lughod sets off on her project to deconstruct and analyze the intersection among feminism, human rights language, and politics with the hope that the actual complicated, diverse, and multifaceted lives of Muslim women can contribute to a critical reflection on the growing movement for women’s rights. In chapter 1, the author sets her sights on Afghanistan, a state well known for its violence and poverty, not to mention the mass suffering of the general population. As she skillfully points out, the plight of Afghan girls and women serves a foundational role in arguments for American intervention. While the Taliban certainly deserve the demonization they have received in the press, so do the numerous other factions that target women as well as religious minorities and ethnic groups like the Hazara. As she reminds us, some of these groups are in “the U.S. backed government” (p. 29) ...